An Analysis of Judges' Considerations in Making Decision About the Case of Application for Marriage Dispensation After the Enactment of Law Number 16 of 2019 Concerning Marriage - Jamaluddin T; Yusuf Djabbar (Al-Bayyinah, 2021)
After the enactment of Law no. 16 of 2019 concerning marriage which substantially regulates the age of marriage. The increase in the age of marriage regulated in the law has become a polemic in the community, so to obtain their rights, a marriage dispensation is proposed. The application for Marriage Dispensation has become a polemic, because the community has not been able to adapt, so with many reasons the judge can grant the request.Therefore, it is urgent to reveal the judge's considerations as a result of the judge's decision on marriage dispensation. This research is a qualitative field research in the field of law. The research location focuses on the study of judges' considerations in applying for a marriage dispensation at Watampone Religious Court.The approach used in this research is a normative juridical approach, an empirical juridical approach and a sociological juridical approach. The analysis used is descriptive qualitative, with the aim of collecting data, described or described in the form of sentence exposure in accordance with the formulation of the problem. The research findings show that judges in examining and adjudicating marriage dispensation cases are carried out based on the Republic of Indonesia Supreme Court Regulation Number 5 of 2019 concerning Guidelines for Adjudicating Applications for Marriage Dispensation.The judge's consideration in making decisionof application for a marriage dispensation emphasizes a persuasive approach and considers the benefit. The implication of this finding is that in the case of dispensation, it should be considered carefully, for the sake of the continuity of the marriage relationship.